2018
DOI: 10.24154/jhs.2018.v13i01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators and pinching on growth and flower yield of African marigold (Tagetes erecta L.)

Abstract: Marigold is one of the commercially exploited flower crop that belong to the family Asteraceae. Presently, in our country the commercial extraction of marigold carotenoids is becoming popular in many states. The production of economical yield and better quality of marigold flowers, requires proper crop management techniques. Crop regulation and flower forcing are important techniques to make the marigold production profitable. This can be done by adopting pinching and application of PGRs. Hence, an experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
4
1
0
Order By: Relevance
“…The delayed flowering in marigold with the application of MH might be due to lesser mitotic activity and preservation of biosynthesis of Gibberellicacid like substances. The present results are in agreement with the findings of Sathappan (2018) and ArtiArha et al, (2019). Similar results were also reported by Girisha et al, (2012), Girwaniet al, (1990 and Khan et al, (2012).…”
Section: Resultssupporting
confidence: 94%
“…The delayed flowering in marigold with the application of MH might be due to lesser mitotic activity and preservation of biosynthesis of Gibberellicacid like substances. The present results are in agreement with the findings of Sathappan (2018) and ArtiArha et al, (2019). Similar results were also reported by Girisha et al, (2012), Girwaniet al, (1990 and Khan et al, (2012).…”
Section: Resultssupporting
confidence: 94%
“…As regard the treatment T 8 (CCC @2000ppm) recorded dry matter production (62.93 g per plant), days taken for flower bud appearance (32.61 days), days to first harvest (51.53 days). Similar findings were noticed by YR Khobragade et al, (2019) [9] and Queenie Syngkrem et al, (2018) [5] observed in white marigold (Tagetes erecta L.) Cv. Vanilla.…”
Section: Yield and Quality Parameterssupporting
confidence: 88%
“…Similar result were noted by C.T. Sathappan (2018) [5] GA 3 @150ppm in African marigold F1 hybrid viz., Gold Benz and Maxima yellow and Ramesh Kumar et al, (2010) [4] in African marigold cv. Pusa Narangi Gainda foliar application of (GA 3 @200ppm) and Mithilesh Kumar et al, (2014) [8] .…”
Section: Yield and Quality Parameterssupporting
confidence: 86%
“…Increase in number of flowers per plant lends support from previous discussion on the flowering parameter such as number of flowers per branch. Comparable finding was stated by Sathappan (2018) in Tagetes erecta.…”
Section: Yield Parameters Number Of Flowers Per Branch and Flowers Pe...supporting
confidence: 69%